2019
DOI: 10.1002/ppsc.201900083
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Calcium‐Oxalate‐ (CaOx‐) Nanocrystal‐Induced Prodeath Autophagy for Attenuating Human Renal Proximal Tubular Epithelial Cell Injury

Abstract: Calcium oxalate (CaOx) stone is the most common type of kidney stone, with a formation process comprising supersaturation, nucleation, growth, aggregation to crystals, and adhesion on renal tubular epithelial cells. CaOx stones generally lead to renal injury; however, the underlying mechanism remains poorly understood. Accumulating evidence suggests that nanosized materials could induce much greater toxicity than bulk materials with the same components. As aggregation to nanocrystals is necessary to form CaOx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…We demonstrated this phenomenon for gold NPs, as an illustrative example here (Figure a), and for many other nanomaterials such as Nd 2 O 3 NPs, ZnO NPs, Nano-C60, and MnO nanocrystals . Similar observations have been made by other laboratories for carbon dots, gold nanospikes, CeO 2 NPs, iron oxide NPs, CaOx nanocrystals, Fe@Au NPs, CoCrMo NPs, and halloysite nanotubes, etc. These nanoparticles, mostly inorganic in nature and undigestible by lysosomal enzymes, may cause disruptive effects on autophagic flux, which refers to the entire process of autophagy from autophagy initiation to autophagy termination.…”
Section: Mechanistic Considerations On the Contrasting Cell Fate Outc...supporting
confidence: 85%
“…We demonstrated this phenomenon for gold NPs, as an illustrative example here (Figure a), and for many other nanomaterials such as Nd 2 O 3 NPs, ZnO NPs, Nano-C60, and MnO nanocrystals . Similar observations have been made by other laboratories for carbon dots, gold nanospikes, CeO 2 NPs, iron oxide NPs, CaOx nanocrystals, Fe@Au NPs, CoCrMo NPs, and halloysite nanotubes, etc. These nanoparticles, mostly inorganic in nature and undigestible by lysosomal enzymes, may cause disruptive effects on autophagic flux, which refers to the entire process of autophagy from autophagy initiation to autophagy termination.…”
Section: Mechanistic Considerations On the Contrasting Cell Fate Outc...supporting
confidence: 85%
“…Many investigations on the mechanism of kidney stone formation have also been conducted, including the theory of renal calcium plaques, the theory of supersaturated crystallization, the theory of matrix, the theory of inhibitor shortage, and the theory of immunological damage ( 30 ). The hypothesis of supersaturation crystallization is the most researched mechanism, and its particular processes include supersaturation, crystal nucleation, aggregation, crystal development, deposition, and stone production ( 31 ). However, the specific mechanism of formation is still unknown, and these studies on the mechanism of formation of kidney stones are all at the molecular biology level, whereas there are few reports on the impact of the external environment that is closely related to human life on the formation of kidney stones, and it has not piqued people's interest.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al showed that autophagy had a protective effect on AKI [8]. Chen et al demonstrated the role of autophagy in CaOx-nanocrystalline-induced cytotoxicity, using autophagy to help design promising strategies to alleviate renal injury in patients with kidney stones [17]. Huang et al found that resveratrol protects podocyte cells from apoptosis by stimulating autophagy in a mouse model of diabetic nephropathy [18].…”
Section: Discussionmentioning
confidence: 99%